Endothelin-1 level in the tear fluid of children with primary congenital glaucoma - L. A. Katargina; N. B. Сhesnokova; N. N. Arestova; A. A. Sorokin; T. A. Pavlenko; O. V. Beznos; O. A. Lisovskaja (Российский офтальмологический журнал, 2023)
Purpose. To analyze the level of endothelin-1 (ET-1) in the tear fluid (TF) of children with primary congenital glaucoma (PCG) and to detect possible correlations between the clinical and the laboratory data. Material and methods. We examined 23 eyes of 15 children with PCG aged between 7 months and 15 years and 3 healthy fellow eyes of these children. 25 eyes of children of same age without glaucoma (somatically healthy with mild hyperopia and/or concomitant strabismus) served as control. A standard ophthalmological examination was supplemented by the flash visual evoked cortical potential, a total and a rhythmic electroretinogram, axial length (AL) echobiometry of the eye, optical coherence tomography of the optic nerve head, enzyme immunoassay (ELISA) of ET-1 level in TF were given. Results. In most children with PCG (95.6 %), the TF level of ET-1 (mean 9.69 ± 3.80 pg/ml) was higher than that in healthy children (4.65 ± 2,02 pg/ml) (p < 0.001). Increased levels of ET-1 (up to 8.90 pg/ml) were also detected in healthy fellow eyes of children with PCG. The mean level of ET-1 in children with PCG aged 3 to 15 years was significantly higher (p< 0.05) lower than in the initial stage. Our study revealed no correlations between the ET-1 level and the degree of retinal nerve fiber layer thinning, or the AL in children with PCG. Conclusion. For the first time, an increased level of ET-1 in the TF in children with PCG was revealed as compared to healthy children. A lower value of ET-1 in the far advanced PCG stage as compared to the initial stage can be explained by long-term chronic eye tissue hypoxia depleting the protective reserves of the eye. Since no obvious correlation between ET-1 level in the TF and clinical and functional data of children with PVG has been found, we cannot definitely view the ET-1 level in the TF as a measure of ischemia degree in PCG. Further studies are needed to obtain reliable correlations.